PERENCANAAN PEMBANGUNAN PASAR TRADISIONAL DI KOTA PADANG PANJANG - Dwi Wahyuni Nilashary; Dadang Mashur (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Creating a local development plan of Padang Panjang Government issued Regulation No. 7 Year 2014 on Medium Term Development Plan (RPJMD), one of which includes the development planning of traditional markets in the city of Padang Panjang. This traditional market development plan created with the aim to improve public visits to these markets and boost the economy of traders who sell in the traditional market area in the city of Padang Panjang this. From observations of researchers in the field of this market is no longer effective for use with the condition that a chaotic and disorganized as this present moment. Buyers who visit has also been much lower since 2012 than in the previous year. The purpose of this research is how the traditional market development plan that has been planned by the government of Padang Panjang and determine the factors that affect the development planning of traditional markets in the city of Padang Panjang.This research was conducted in the Office of Market Management Padang Panjang, by using descriptive qualitative research, with data collection techniques of observation and interviews. This research was conducted by using the theory according to Munir ie policy making, programming and budgeting.Results of this study concluded that the construction of the traditional market in the city of Padang Panjang is not going well. This is evidenced by the slow implementation of development of traditional markets where construction according RPJMD regulation should have been started since the year 2013, but until now the market development is still in the form of planning. This happens because many traders are still concerned about the development of this market and the weakness of the government in implementing development policies this traditional market.Keywords: Planning, Development, Traditional Market